Electron microscope study of the base sequence homology between simian virus 40 and human papovavirus BK. - Newell, N (1978)
The base sequence homology between the genomes of simian virus 40 (SV40) and human papovavirus BK (BKV) was studied by the heteroduplex method of Ferguson and Davis (J. Mol. Biol. 94:135-149, 1975). When mounted for microscopy in 30% formamide (Tm-35 degrees C), BKV/SV40 heteroduplexes were an average of 92% double-stranded and contained only two small nonhomologous regions that mapped near the junctions between the early and late regions of the SV40 Genome. At higher formamide concentrations, the fraction of duplex DNA in the BKV/SV40 heteroduplexes decreased, indicating significant base mismatching in the homologous regions. The strongest regions of homology were located in the late region.